Improving Buffalo Milk Production to Sustain the Production of Dadih by Small Farmers in West Sumatera - B, Wirdahayati R (Indonesian Animal Sciences Society, 2007)
The swamp buffalo which is found in many Asian regions is mainly raised for meat and draft purposes. However, in West Sumatera, it is also milked and the milk is mostly consumed as âdadihâ, a well known traditional product from this area. Dadih is actually a product made from fresh buffalo milk, which is kept in bamboo tube for about 2-3 days under room temperature, without any application or addition of bacteria starter although the end product of this fermentation contains various bacteria, mould and khamir. As the natural fermented milk product, dadih is white in colour and the curd texture like tofu, tastes like yoghurt, and it is generally served as a complementing meal in some traditional occasion as well as delicacy from West Sumatera. Dadih is highly nutritive product, protein and fat contents are higher than those of yoghurt, rich in amino acids and bacteria such as Lactobacillus sp. and low in cholesterol. The raw material for dadih is limited due to the low productivity of fresh buffalo milk which is generally collected for about 0.5 â 2.0 litres/head/day. The effort in sustaining âdadih productâ is directed to the improving the management of the buffalo condition particularly those in lactating period. Feeding improvement is recommended in order to provide an adequate milk for raising its calf and to be milked for making dadih and to support the optimal reproductive activity of the buffalo dam. In future, the assessment on âdadihâ should also include the packaging improvement which can improve and prolong the storage time for the benefit of marketing purposes. Â Key words: Buffalo, dadih, milk, feed supplement, West Sumatera